Comparison of methane, nitrous oxide fluxes and CO2 respiration rates from a Mediterranean cork oak ecosystem and improved pasture - Shvaleva, Alla; e Silva, Filipe; Costa, Joaquim Miguel; Correia, Alexandra; Anderson, Margaret; Lobo-do-Vale, Raquel; Fangueiro, David; Bicho, Catarina; Pereira, Joo Santos; Chaves, Maria Manuela; Skiba, Ute; Cruz, Cristina (PLANT AND SOIL, 2014)
During the recent decades, cork oak (Q. suber) mortality has been increasing in Mediterranean oak woodland endangering the economical and environmental sustainability of the ``montado{''} ecosystem. This fact in combination with climate change and conversion of forestland to pasture may significantly affect the soil-atmosphere greenhouse gases (GHGs) exchange. Our study evaluates the impact of oak trees as compared to pasture on net ecosystem GHG (CH4, N2O, and CO2) exchange as well as the main environmental factors influencing this exchange. We used field chamber measurements for the collection of GHGs under three different conditions: 1) open area (OA), 2) under tree canopy area (UC) and 3) improved pasture (IP). Experiments were done under typical Mediterranean climate at central Portugal in 2010 and 2011. The UC had higher nitrification potential, soil C/N ratio, electrical conductivity, litter input and soil organic matter (SOM) than OA and IP. SOM positively correlated with soil CH4 and N2O fluxes but not with soil CO2 respiration rates. Soil water content (SWC) drives both CH4 and N2O fluxes. Under certain conditions, when SWC reached a threshold (7 % for CH4 and 3 % for N2O) the result was net uptake and that net uptake increased with SWC. This was the case for the UC and OA. Conversely, for the IP soil water content above 4 % promoted net CH4 release. Our results show that cork oak influences soil properties and consequently GHGs fluxes. In the UC the input of litter for SOM together with soil moisture, favoured microbiological activity and related GHGs fluxes. Soil temperature is a secondary factor in the studied conditions. Our results also emphasized the potential impact posed by decreased cork oak tree density in the functioning of the ``montado{''} ecosystem.
Keywords: evergreen oak; Greenhouse gases; litter; Mediterranean; organic matter; Root density

Cork oak physiological responses to manipulated water availability in a Mediterranean woodland - Besson, Cathy Kurz; Lobo-do-Vale, Raquel; Rodrigues, Maria Lucília; Almeida, Pedro; Herd, Alastair; Grant, Olga Mary; David, Teresa Soares; Schmidt, Markus; Otieno, Denis; Keenan, Trevor F.; Gouveia, Célia; Mériaux, Catherine; et al. (Agricultural and Forest Meteorology, 2014)
This study details the physiological responses of cork oak (Quercus suber L.) to manipulated water inputs. Treatments named as dry, ambient and wet, which received 80, 100 and 120% of the annual precipitation, respectively, were applied to a Mediterranean woodland in southern Portugal. Tree ecophysiology and growth were monitored from 2003 to 2005. The impacts of the water manipulation were primarily observed in tree transpiration, especially dur- ing summer drought. Rainfall exclusion reduced the annual stand canopy transpiration by 10% over the 2-year study period, while irrigation increased it by 11%. The accumulated tree transpiration matched precipitation in spring 2004 and 2005 at the stand level, suggesting that cork oak trees rely on precip- itation water sources during the peak of the growing season. However, during the summer droughts, by trees appeared unaffected by the extreme drought of 2005. Our study shows that cork oak rapidly and completely recovered from the extreme dry year of 2005 or from rainfall exclusion. Our results support the eco-hydrological equilibrium theory by which plant acquire complementary protective mechanisms to buffer the large variability in water availability experienced in semi-arid ecosystems. In optimizing their structural biomass increase in response to increasing drought stress, cork oak trees succeeded in restricting water losses to maintain the minimum leaf water potential above the critical threshold of xylem embolism, though with narrower hydraulic safety margins in 2005. Our findings highlight cork oak’s sensitivity to the amount and timing of late spring precipitation. This could be critical as future climate scenarios predict a reduction of spring precipitation as well as enhanced severity of droughts in the Iberian Peninsula by the end of the 21st century. In inducing water stress before the onset of summer droughts, the predicted spring precipitation decline could drive the species closer to the threshold of catastrophic xylem embolism at the peak of the drought period. groundwater was the main water source for trees. Despite the significant differences in soil water content and tree transpiration, no treatment effects could be detected in leaf water potential and leaf gas exchange, except for a single event after spring irri- gations in the very dry year 2005. These irrigations were intentionally delayed to reduce dry spell duration during the peak of tree growing season. They resulted in an acute positive physiological response of trees from the wet treatment one week after the last irrigation event leading to a 32% raise of stem diame- ter increment the following months. Our results suggest that in a semi-arid environment precipitation changes in spring (amount and timing) have a stronger impact on cork oak physiology and growth than an overall change in the total annual precipitation. The extreme drought of 2005 had a negative impact on tree growth. The annual increment of tree trunk diameter in the ambient and dry treatments was reduced, while it increased for trees from the wet treatment. Water shortage also significantly reduced leaf area. The latter dropped by 10.4% in response to the extreme drought of 2005 in trees from the ambient treatment. The reduction was less pronounced in trees of the wet treatment (−7.6%), and more pronounced in trees of the dry treatment (−14.7%). Cork oak showed high resiliency to inter-annual precipitation variability. The annual accumulated tree transpiration, the minimum midday leaf water potential and the absolute amount of groundwater used
From Duplicate 1 ( Cork oak physiological responses to manipulated water availability in a Mediterranean woodland - Besson, Cathy Kurz; Lobo-do-Vale, Raquel; Rodrigues, Maria Lucília; Almeida, Pedro; Herd, Alastair; Grant, Olga Mary; David, Teresa Soares; Schmidt, Markus; Otieno, Denis; Keenan, Trevor F; Gouveia, Célia; Mériaux, Catherine; Chaves, Maria Manuela; Pereira, João S )From Duplicate 1 ( Cork oak physiological responses to manipulated water availability in a Mediterranean woodland - Besson, Cathy Kurz; Lobo-do-Vale, Raquel; Rodrigues, Maria Lucília; Almeida, Pedro; Herd, Alastair; Grant, Olga Mary; David, Teresa Soares; Schmidt, Markus; Otieno, Denis; Keenan, Trevor F; Gouveia, Célia; Mériaux, Catherine; Chaves, Maria Manuela; Pereira, João S )The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Gas exchange; Precipitation change; Quercus suber; Soil moisture; Throughfall manipulation; Tree transpiration

Photosynthesis of Quercus suber is affected by atmospheric NH3 generated by multifunctional agrosystems - Pintó-Marijuan, Marta; Da Silva, Anabela Bernardes; Flexas, Jaume; Dias, Teresa; Zarrouk, Olfa; Martins-Loução, Maria Amélia; Chaves, Maria Manuela; Cruz, Cristina (Tree Physiology, 2013)
Montados are evergreen oak woodlands dominated by Quercus species, which are considered to be key to biodiversity conservation and ecosystem services. This ecosystem is often used for cattle breeding in most regions of the Iberian Peninsula, which causes plants to receive extra nitrogen as ammonia (NH3) through the atmosphere. The effect of this atmospheric NH3 (NH3atm) on ecosystems is still under discussion. This study aimed to evaluate the effects of an NH3atm concentration gradient downwind of a cattle barn in a Montado area. Leaves from the selected Quercus suber L. trees along the gradient showed a clear influence of the NH3 on δ13C, as a consequence of a strong limitation on the photosynthetic machinery by a reduction of both stomatal and mesophyll conductance. A detailed study of the impact of NH3atm on the photosynthetic performance of Q. suber trees is presented, and new mechanisms by which NH3 affects photosynthesis at the leaf level are suggested.
10.1093/treephys/tpt077
Keywords: carbon isotopic discrimination; Cork oak; mesophyll conductance; Stomatal conductance

Temperature stress effects in Quercus suber leaf metabolism. - Chaves, Inês; Passarinho, José António P; Capitão, Cláudio; Chaves, Maria Manuela; Fevereiro, Pedro; Ricardo, Cândido P P (Journal of plant physiology, 2011)
Based on projections that climate changes are will intensify in the near future, it is important to understand how plants respond to climate. Consequently, we have been studying the effect of contrasting temperatures on leaf metabolism of Quercus suber, an important Mediterranean oak. Potted plants were grown under controlled conditions for 53 days at 28°C or 10°C. The accumulation of major soluble metabolites was analyzed by NMR. The relative levels of transcripts of genes encoding key enzymes of the shikimate and phenylpropanoid pathway (CS, PAL, CAD and ChS) were examined by means of quantitative, real-time RT-PCR. At 10°C, in the pre-existing leaves, the concentrations of sucrose, quercitol and catechin were higher, as were PAL and ChS transcripts. At 28°C, however, it was the concentration of quinic acid that was higher, as were the concentrations of CS and CAD transcripts. We conclude that contrasting temperatures greatly influence Q. suber metabolism and that a deeper analysis of the effects of more extreme temperatures is needed to understand the possible effects of temperature changes on Q. suber metabolism and physiology.
Keywords: Abiotic stress response; Cork oak; Phenol metabolism; Secondary metabolism

Carbon and nitrogen winter storage and remobilisation during seasonal flush growth in two-year-old cork oak (Quercus suber L.) saplings - Cerasoli, Sofia; Maillard, Pascale; Scartazza, Andrea; Brugnoli, Enrico; Chaves, Maria Manuela; Pereira, João Santos; Erasolia, Sofia C.; Aillardc, Pascale M.; Cartazzad, Andrea S.; Rugnolid, Enrico B.; Havesa, Maria Manuela C.; Ereiraa, João Santos P. (Ann. For. Sci., 2004)
A dual long-term 13C and 15N labeling was used to assess the contribution of winter assimilated carbon (C) and nitrogen (N) for the spring growth flush of two-year-old cork oak plants. Changes in concentrations and partitioning of winter assimilated C and N, total C and N, and total-non-structural carbohydrates were followed from January to August in the various plant parts (first year and second year leaves, stem, branches, coarse and fine roots). No loss of winter C and N was observed with time suggesting that winter assimilates are retained within the plant and contribute to storage. A strong mobilisation of C and N was demonstrated from first year leaves and fine roots during the spring growth flush. Leaves from the second year and, to lesser extent, branches acted as sinks for winter C and N. At the beginning of the new leaf growth, a significant decrease in starch concentration occurred in first year leaves. In August, before leaf fall we observed also a mobilisation from first year to second year leaves, of N assimilated after labeling. We conclude that under these experimental conditions, both winter and current C and N were used for the spring growth flush of the cork oak plants. The foliage grown during the previous year was a source of winter and recently assimilated N and a source of C from recent assimilates for the new growth in the spring.
Keywords: 13C labeling; 15N labeling; carbohydrates; Quercus suber; remobilisation

Carbon and nitrogen winter storage and remobilisation during seasonal flush growth in two-year-old cork oak (Quercus suber L.) saplings - Cerasoli, Sofia; Maillard, Pascale; Scartazza, Andrea; Brugnoli, Enrico; Chaves, Maria Manuela; Pereira, João Santos; Erasolia, Sofia C; Aillardc, Pascale M; Cartazzad, Andrea S; Rugnolid, Enrico B; Havesa, Maria Manuela C; Ereiraa, João Santos P (Ann. For. Sci., 2004)
A dual long-term 13C and 15N labeling was used to assess the contribution of winter assimilated carbon (C) and nitrogen (N) for the spring growth flush of two-year-old cork oak plants. Changes in concentrations and partitioning of winter assimilated C and N, total C and N, and total-non-structural carbohydrates were followed from January to August in the various plant parts (first year and second year leaves, stem, branches, coarse and fine roots). No loss of winter C and N was observed with time suggesting that winter assimilates are retained within the plant and contribute to storage. A strong mobilisation of C and N was demonstrated from first year leaves and fine roots during the spring growth flush. Leaves from the second year and, to lesser extent, branches acted as sinks for winter C and N. At the beginning of the new leaf growth, a significant decrease in starch concentration occurred in first year leaves. In August, before leaf fall we observed also a mobilisation from first year to second year leaves, of N assimilated after labeling. We conclude that under these experimental conditions, both winter and current C and N were used for the spring growth flush of the cork oak plants. The foliage grown during the previous year was a source of winter and recently assimilated N and a source of C from recent assimilates for the new growth in the spring.
Keywords: 13C labeling; 15N labeling; carbohydrates; Quercus suber; remobilisation